Techno-economic assessment of an integrated algal biorefinery - Erdinçler, Begüm. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2021., 2021)
There is an urgent global need to access sustainable energy sources as the supply-demand imbalance of non-renewable energy resources is one of the most critical issues of humankind. All alternate solutions offered to replace fossil-based non-renewables must be both economically viable and environmentally sustainable. In this respect, techno-economic assessments play crucial roles in achieving economic viability while covering the whole production pipeline of the offered product. Algae-based biofuels are strong candidates compared to other biofuels concerning their higher biomass yield, shorter growth cycle and the capability of year-round cultivation in marine and brackish water. Despite these advantages, high energy requirements and costly equipment increase both capital and operational expenses, weakening the viability of commercialization of algae-based biofuels. To address this issue, integrated algal biorefineries have become prominent; implementing production of multi-valorized, value-added products, while optimizing the usage of resources from different feedstocks. To assess the viability, this study conducts a techno-economic assessment of a full-scale carbon-negative integrated algal biorefinery for bio-jet fuel, astaxanthin, beta-carotene and Spirulina powder production. Viable prices for bio-jet fuel commercialization were calculated to be 3.227-9.011$/ton for 50 % blend (with commercial Jet A-1 fuel), 866-1.444$/ton for 5 % blend, 656- 771$/ton for 1 % blend without carbon credit. With the addition of carbon credit, the prices were found to decrease to 3.199-8.807$/ton for 50 % blend, 838-1.240$/ton for 5 % blend and 567- 628$/ton for 1 % blend. Minimum viable prices for astaxanthin, beta-carotene and Spirulina powder were calculated as 850$/kg, 43,50$/kg, and 307$/kg, respectively.
Keywords: Biomass energy.; Algae -- Biotechnology.